Study of bimetallic silver-cobalt phosphide nanoparticles using in situ TEM - Brink,Fanny (2025)
Achieving efficient production of hydrogen through the hydrogen evolution reaction is an attractive source of non-fossil fuel. However, this reaction is inefficient and therefore requires catalysts with the most commonly used one being Pt. Due to the high cost and rarity of Pt, research into alternative catalyst materials such as transition metal phosphides has been conducted in the recent years. An example of such materials are cobalt phosphides, which could serve as a more cost-efficient and abundant alternative to the noble metal. Furthermore, it is theorized that the catalytic activity of cobalt phosphide compounds can be enhanced due to synergy effects when combined with Ag in bimetallic nanoparticles. The physical and chemical properties of the Ag-Co-P nanoparticles can be tuned by varying composition, morphology and crystal structure. However, the impact of synthesis conditions on morphology, composition and crystal structure is not yet well understood. In this thesis, the effect of formation of Ag-Co-P nanoparticles was investigated by examining the phosphorization of Ag-Co nanoparticles with two different compositions in situ. This was done by supplying phosphine gas to bimetallic Ag-Co nanoparticles and investigating them in real time using an environmental transmission electron microscope. By performing the synthesis at a variety of different phosphine flows it was possible to observe that the rate of compositional transformation of Co to CoP compounds correlated with phosphine flow. However, the phosphine flow had little to no impact on the specific composition or crystal structure of the resulting nanoparticles. The nanoparticles appeared polycrystalline and one crystal structure consistently identified was orthorhombic CoP. It was however found that increasing the temperature of the sample after the transformation could change the composition and crystal structure of the nanoparticles. The morphology of the nanoparticles after transformation was found to be different depending on the composition of the bimetallic particles before phosphine was supplied, where a core/shell-like structure was observed for nanoparticles with a smaller fraction of Ag. The results of this project provides a base for further investigations of bimetallic Ag-Co-P nanoparticles and development of advanced nanoparticle catalysts for the hydrogen evolution reaction.
Keywords: ETEM; in situ; HER: cobalt phosphide; materials chemistry